Hybrid inertial proximal algorithm for the split variational inclusion problem in Hilbert spaces with applications. (4th May 2017) - Chuang, Chih-Sheng
Abstract : In this paper, we present hybrid inertial proximal algorithms for the split variational inclusion problems in Hilbert spaces, and provide convergence theorems for the proposed algorithms. In fact, an inertial type algorithm was proposed as an acceleration process. As application, we study split minimization problem, split feasibility problem, relaxed split feasibility problem and linear inverse problem in real Hilbert spaces. Finally, numerical results are given for our main results.